Paper roses : a novel - Cabot, Amanda, 1948- (Cabot, Amanda, 1948- Texas dreams, 2009)
"Leaving the past behind in Philadelphia, mail-order bride Sarah Dobbs arrives in San Antonio ready to greet her groom - a man she has never met but whose letters, her paper roses, have won her heart from afar. But there is a problem - Austin Canfield is dead, and Sarah cannot go back East. As Sarah tries to reconcile herself to a future that is drastically changed, Austin's brother, Clay, wants nothing more than to shake the Texas dust from his boots, but first he must find his brother's killer. And then there's Sarah."--Back cover.